Effect of external volume expansion on the survival of fat grafts - Raghuveer Reddy; Subramania Iyer; Mohit Sharma; Sundeep Vijayaraghavan; P. Kishore; Jimmy Mathew; A. K. K. Unni; P. Reshmi; Rakesh Sharma; Chaya Prasad (Indian Journal of Plastic Surgery)
Introduction: External volume expansion (EVE) is one method, which has been utilised for increasing the survival of adipose tissue grafts. EVE releases positive pressure from the graft and also induces intense levels of edema that decreases diffusion of metabolites essential for graft survival initially. The ideal timing of external volume expansion in relation to the injection of the fat to facilitate survival is not yet clear. Aims and Objectives: This study was undertaken to evaluate and compare the efficacy of external volume expansion applied at variable time points in relation to the injection of the fat. Materials and Methods: Athymic mouse was the animal model and human lipo-aspirate mixed with PRP was used as graft. An indigenous dome shaped silicone device was fabricated to deliver a negative pressure of -30 mm of Hg. The EVE was applied at variable time intervals. At the end of 4 weeks visual, histological and radiological features of the injected fat were compared. The adipose tissue was stained with human vimentin to ascertain the origin of the retained fat. Results: All the grafts, which had EVE, had significantly better volume retention and vascularity. The groups which underwent a delayed EVE or prior expansion followed by concomitant graft injection and expansion showed the most optimal vascularity and graft retention. Conclusions: A delayed EVE or prior expansion followed by concomitant graft injection and expansion may be the most ideal combinations to optimize graft take. However, on account of the relatively small sample size, there was a limitation in drawing statistically significant conclusions for certain variables.